Prevalence Of Affected Bowel Syndrome Among Children Of Different Ages - Kholikova Gulnoz Asatovna (Genius Journals, 2025)
The article presents new data on the prevalence and diagnostic criteria of irritable bowel syndrome in children. The main objective of our study was to analyze the prevalence of irritable bowel syndrome (IBS) among children and assess the risk factors for IBS development. During 2023-2024, the types of IBS and symptoms confirming it were analyzed in children treated in the gastroenterology department of the regional multidisciplinary children's medical center based on the Rome IV criteria. According to according to, out of 228 children aged 4 to 16 years who soul treatment in the emergency department of the regional multidisciplinary children's medical center with abdominal pain, after examination by a gastroenterologist and a special examination, 102 children were diagnosed with irritable bowel syndrome. According to the Rome IV criteria, most of the surveyed children had a predominance of IBS-3 (anticipation) type, IIS highest frequency corresponded to the autumn-winter season.
Keywords: IBS-C; predominantly constipation; gastroenterology